Wikipedia: 17 Years of Free Knowledge (2018)
The editor of the virtual encyclopedia, Wikipedia, Juan Sebastián recounts his experience and work with Wikipedia that has become his passion coming out of the spontaneity of wanting topics of his interest on the web to be found. There is also very good data from the members of this community from their roles to page figures as such and their alliances.